Теоретико-методичні домінанти оцінювання результатів позиціонування територіальних громад Сходу України - Rohozian, Yuliia; Zablodska, Daria; Liashenko, Pavlo (Dr. Viktor Koval, 2021)
Introduction. The issues of increasing the local territories competitiveness in recent years have gained great importance, given the dynamics of trends in the economic ties localization. For Ukrainian territorial communities, especially suffering from the consequences of hostilities in the east of the country, an important task is to form their positive and attractive image by using such a marketing tool as the territory positioning. This process bases on the identification of unique economic, social and environmental characteristics that can create the foundation for the formation of a positive and attractive community image in order to increase its competitiveness. Aim and tasks. The aim of the article is to substantiate the theoretical and methodical dominants evaluation for the positioning results of territorial communities in the eastern Ukraine to form their positive image and increase competitiveness. This aim reveals through the prism of tasks, which are to substantiate the architectonic foundations for positioning territorial communities, defining archetypal components for assessing the results of positioning territories and conducting their rating assessment. Results. The analysis of foreign and domestic scientific and theoretical heritage demonstrates an insufficient level of research into the issues of theoretical and methodical support for assessing the results of the territorial communities positioning. It made possible to substantiate their architectonic theoretical and methodical dominants with the allocation of a basic and auxiliary level to obtain a positive effect. The article proposes the archetype of community positioning parameters, which display in 17 indicators in terms of sustainable development. This system of parameters formed the basis for the rating assessment of positioning results by defining quantified and reference indicators reflecting the current economic, social and environmental positions of the local territory. Conclusions. The results of the rating assessment using the example of the Bilovodsk community confirmed the imbalance of its positioning between economic, social and environmental positions, with the latter being given priority. It proposes to solve this problem by adjusting the economic and social parameters of the community's positioning, changing the emphasis on those indicators of socio-economic development, that better characterize its unique features, which will help attract potential consumers and increase the level of its competitiveness.